Problem Based Learning and Diorama Media in Primary Science Education: Pembelajaran Berbasis Masalah dan Media Diorama pada Pendidikan Sains Dasar - Nabila Syifa Ramadhani; Ibadullah Malawi; Sri Budyartati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The integration of Natural and Social Sciences in the independent curriculum requires students to actively analyze and reason about concrete phenomena rather than passively memorizing facts. Specific Background However, low active participation and predominantly verbal instruction make abstract concepts, such as planetary rotation, difficult for sixth-grade cohorts to comprehend. Knowledge Gap Previous literature predominantly focuses on other grade levels or tool development, leaving a limited understanding of how interactive models shape cognitive outcomes specifically for sixth-grade students. Aims This study investigates the integration of interactive pedagogy supported by spatial-visual tools on the cognitive outcomes of sixth-grade students regarding planetary rotation at SDN Klagen Serut 1. Results Utilizing a quasi-experimental Nonequivalent Control Group Design with 38 students, data analysis via an Independent Samples t-test revealed a significance value of 0.000. The experimental group achieved a higher post-test mean score of 88.00 compared to the control group's 69.78. Novelty This research specifically isolates the synergistic function of contextual pedagogy and three-dimensional visual tools in addressing the complex academic demands of sixth-grade cohorts. Implications Educators can utilize this supported pedagogical model as a strategic alternative to visualize abstract concepts, foster active student engagement, and elevate comprehensive cognitive results in primary education. Highlights The interactive pedagogy yielded a final mean score of 88 over the control group. Visual spatial tools successfully translated abstract planetary rotation concepts for sixth grade learners. Contextual educational scenarios directly elevated cognitive results among participating students. Keywords Diorama Media; Earth Rotation; Natural And Social Sciences; Problem Based Learning; Cognitive Results